2015
DOI: 10.1002/pam.21862
|View full text |Cite
|
Sign up to set email alerts
|

Do Industrial Tax Abatements Spur Property Value Growth?

Abstract: Despite ongoing debate regarding the effectiveness of tax abatements, Michigan's Industrial Facilities Tax (IFT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Wassmer (1992) found that property tax abatements are costly for whichever jurisdiction that winds up paying for them. Kang et al (2015) found that tax abatements contribute to property value growth, but that the fiscal benefits pale in comparison to the costs. Landers (2006) found that enterprise zones raise the property value within them, but that the more of them there are, the less revenue benefits each generates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wassmer (1992) found that property tax abatements are costly for whichever jurisdiction that winds up paying for them. Kang et al (2015) found that tax abatements contribute to property value growth, but that the fiscal benefits pale in comparison to the costs. Landers (2006) found that enterprise zones raise the property value within them, but that the more of them there are, the less revenue benefits each generates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While cooperation among jurisdictions can bring tremendous benefits, competition and fragmentation can make it a very risky endeavor (Feiock, Lee, and Park 2012). Research has shown that state and local tax choices can influence industrial and other economic activity (Kang, Reese, and Skidmore 2016; Thom 2018). Thom (2018) examined state incentives to lure the motion picture industry away from California and New York, finding small and mixed effects across a series of outputs, with no effect on outcomes such as industry concentration or gross state product.…”
Section: Economic Development and Tax Policymentioning
confidence: 99%
“…In contrast, property tax abatements offered to ameliorate Michigan’s Industrial Facilities Tax were associated with property value increases, suggesting positive economic benefits. However, the authors noted that the estimated fiscal benefits of the property value increases were small compared with the foregone tax revenue (Kang et al, 2016).…”
Section: Background: Property Tax Abatement and Its Impactsmentioning
confidence: 99%